Global Investment Competitiveness Report 2019/2020 : Rebuilding Investor Confidence in Times of Uncertainty - World Bank Group (Washington, DC: World Bank, 2020)
The Global Investment Competitiveness Report 2019/2020 provides novel analytical insights, empirical evidence, and actionable recommendations for governments seeking to rebuild investor confidence in times of uncertainty. It focuses on the role of foreign direct investment (FDI) in alleviating the impact of the COVID-19 crisis and boosting countries’ economic resilience. It highlights FDI’s contributions to providing a critical source of external finance, creating jobs, lifting people out of poverty, and raising productivity. The report presents results of a survey of more than 2,400 business executives representing multinational corporations in 10 large developing countries: Brazil, China, India, Indonesia, Malaysia, Mexico, Nigeria, Thailand, Turkey, and Vietnam. Results of the survey, as well as the report’s new global database of regulatory risk, highlight the critical role of government actions in reducing investor risk and increasing policy predictability for rebuilding investor confidence. The report also assesses the impact of FDI on poverty, inequality, employment, and business performance using firm- and household-level evidence from various countries. It shows that FDI in developing countries yields benefits to firms and workers—including more and better-paid jobs—but governments need to remain vigilant about possible adverse consequences on income distribution. Lastly, the report articulates priorities for investment promotion agencies and other stakeholders seeking to strengthen their countries’ investment competitiveness and leverage FDI for a robust economic recovery.